Emergence of fluoroquinolone resistance in Neisseria gonorrhoeae isolates from four clinics in three regions of Kenya. - Lagace-Wiens, P; Duncan, S; Kimani, J; Thiong'o, A; Shafi, J; McClelland, S; Sanders, E; Zhanel, G; Muraguri, N; Mehta, S (2012)
We have recently reported high levels of fluoroquinolone resistance in a single region of Kenya. In this article, we report high prevalence of fluoroquinolone resistance (53.2%) in Neisseria gonorrhoeae isolates from 4 clinics in 3 additional regions of Kenya. These findings highlight the need to change first-line treatment in these settings and the need to evaluate empirical management guidelines for treatment of gonococcal infection in Kenya.